2020
DOI: 10.1111/acem.14009
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Criteria for COVID‐19 Testing of Heath Care Workers

Abstract: Background: Symptom criteria for COVID-19 testing of heath care workers (HCWs) limitations on testing availability have been challenging during the COVID-19 pandemic. An evidence-based symptom criteria for identifying HCWs for testing, based on the probability of positive COVID-19 test results, would allow for a more appropriate use of testing resources. Methods:This was an observational study of outpatient COVID-19 testing of HCWs. Prior to testing, HCWs were asked about the presence of 10 symptoms. Their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
7
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 21 publications
7
64
7
5
Order By: Relevance
“…Our results agree with Clemency et al [23] concerning the diagnostic characteristics of symptoms (high specificity and negative predictive value) for anosmia and ageusia. We found the level of sensitivity similar to that reported by Brandstetter et al (51.6% for anosmia) [15] and higher to those reported by Lan et al (15.6% for anosmia/ageusia) [12] and Wee et al (22.7% for olfactory and taste disorders) [24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with Clemency et al [23] concerning the diagnostic characteristics of symptoms (high specificity and negative predictive value) for anosmia and ageusia. We found the level of sensitivity similar to that reported by Brandstetter et al (51.6% for anosmia) [15] and higher to those reported by Lan et al (15.6% for anosmia/ageusia) [12] and Wee et al (22.7% for olfactory and taste disorders) [24].…”
Section: Discussionsupporting
confidence: 93%
“…We found the level of sensitivity similar to that reported by Brandstetter et al (51.6% for anosmia) [15] and higher to those reported by Lan et al (15.6% for anosmia/ageusia) [12] and Wee et al (22.7% for olfactory and taste disorders) [24]. Regarding specificity concerns, our results are similar to those reported by Lan et al (97%) [12], Brandstetter et al (97.6%) [15], and Wee et al (99.7%) [23]. PPV and NPV in our study were quite high.…”
Section: Discussionsupporting
confidence: 87%
“…Further, in the UK, a screening program on asymptomatic HWs in a teaching hospital swabbed and tested by RT-PCR was carried out, and 3% tested positive for SARS-CoV-2 infection [26], thus keeping in step with our results. On the other hand, a study on SARS-CoV-2 testing in HWs found a symptoms-related performance of diagnosis by RT-PCR [27]; therefore, great attention must be paid to which symptoms should be taken into account for building the screening decisional algorithm. Taken together, these data suggest that proactive molecular screening strategies including asymptomatic as well as symptomatic HWs should be a priority at the national and international levels.…”
Section: Discussionmentioning
confidence: 99%
“…the patient will be considered as a probable case, therefore isolation and study of contacts will be indicated. Although there are no specific symptoms and signs of SC2 infection, the frequency of clinical manifestations in the different published series makes it possible to classify the symptoms and signs that in adults better predict the probability of positivity in a screening test for SC2 (Table 2) [33,34].…”
Section: Algorithms On the Implementation Of Microbiological Techniqumentioning
confidence: 99%